1982
DOI: 10.2151/jmsj1965.60.1_78
|View full text |Cite
|
Sign up to set email alerts
|

The Response of a Hemispheric Multi-Level Model Atmosphere to Forcing by Topography and Stationary Heat Sources (I) Forcing by Topography

Abstract: The standing waves responding to forcing by the Hemispheric topography are investigated by means of a quasi-geostrophic, steady state, 34-level model, with Rayleigh friction,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 19 publications
(8 reference statements)
1
16
0
Order By: Relevance
“…This theory also suggests that large-scale waves (zonal wave number = 1, 2, 3) are more likely to propagate upwards because their associated critical wind speeds are higher. Studies by Matsuno (1970), Lin (1982), Huang and Gambo (2002), Limpasuvan and Hartmann (2000), Hu and Tung (2002), and Dickinson (1969) not only confirmed this theory but also stressed the importance of vertical shear of the zonal mean zonal wind as well as the vertical gradient of the buoyancy frequency for vertical propagation of large-scale waves. Matsuno (1970) introduced the refractive index for stationary planetary waves (or alternatively vertical wave number) as a diagnostic tool for studying the influence of the background zonal flow on planetary wave propagation.…”
Section: Introductionmentioning
confidence: 69%
“…This theory also suggests that large-scale waves (zonal wave number = 1, 2, 3) are more likely to propagate upwards because their associated critical wind speeds are higher. Studies by Matsuno (1970), Lin (1982), Huang and Gambo (2002), Limpasuvan and Hartmann (2000), Hu and Tung (2002), and Dickinson (1969) not only confirmed this theory but also stressed the importance of vertical shear of the zonal mean zonal wind as well as the vertical gradient of the buoyancy frequency for vertical propagation of large-scale waves. Matsuno (1970) introduced the refractive index for stationary planetary waves (or alternatively vertical wave number) as a diagnostic tool for studying the influence of the background zonal flow on planetary wave propagation.…”
Section: Introductionmentioning
confidence: 69%
“…The buoyancy frequency represents the stability of atmosphere. In some other studies, the buoyancy frequency was treated as a constant (Matsuno, 1970;Huang and Gambo, 1982;Andrews et al, 1987), or as a variable of altitudes only (Chen and Robinson, 1992;Limpasuvan and Harmann, 2000;Hu and Tung, 2002). Chen and Robinson (1992) found that the variation of N 2 is not as negligible as it has been hypothesized in other applications (Matsuno, 1970;Andrews et al, 1987).…”
Section: Boreal Wintermentioning
confidence: 99%
“…After the theoretical study of Charney and Drazin (1961), the refractive index of stationary planetary waves was firstly introduced as a diagnostic tool by Matsuno (1970) and has frequently been applied by a number of researchers thereafter (Lin, 1982;Huang and Gambo, 1982;Hu and Tung, 2002;Mukougawa and Hirootka, 2004;etc. ) to investigate planetary wave propagation.…”
Section: Q LI Et Al: Climatology Of Stationary Planetary Waves In Nmentioning
confidence: 99%
“…In Part I of this paper (Huang and Gambo, 1982), a quasi-geostrophic, steady-state 34-level model with Rayleigh friction, Newtonian cooling effect and horizontal kinematic thermal diffusivity included in a spherical coordinate system was used to examine the standing waves responding to forcing by the Hemispheric topography in winter. In this paper, however, we discuss the standing waves responding to forcing by the Hemispheric topography and the stationary heat sources in winter.…”
Section: Introductionmentioning
confidence: 99%